The Comparison of Candida spp. Colonization on Psoriasis Vulgaris Patient and Control - Amanda Gracia Manuputty; Dwi Murtiastutik; Sawitri Sawitri; Muhammad Yulianto Listiawan; Rahmadewi Rahmadewi; Afif Nurul Hidayati; Pepy Dwi Endraswari; Evy Ervianti (Faculty of Medicine, Universitas Airlangga, 2021)
Background: Psoriasis is an inflammatory, chronic, and recurring skin disease that affects patient’s quality of life. Environment, drugs, and infections in the form of antigen and toxin such as Candida spp. are assumed responsible for triggering and exacerbating psoriasis. Purpose: To compare the prevalence of skin colonization of Candida spp. on psoriasis vulgaris patient and control. Methods: This study was observational analytic research involving 33 psoriasis vulgaris patients and 33 healthy individuals. They were matched up based on sex, age, and lesion location. Swab of skin lesions on the Koebner area of both groups was cultured on CHROMagar media. Candida spp. was later identified and the colonization was calculated. Result: Candida spp. was found on 51.5% of lesions in psoriasis vulgaris patients and 21.2% in the control group with a significant difference of p < 0.05. The average colony number of Candida spp. in psoriasis vulgaris group was lower than the control group with no significant difference of p > 0.05. The predominant Candida spp. in the psoriasis vulgaris and control groups was Candida krusei, which were 35.5% and 85.6%, respectively. No significant difference between sex, age, period of complaints, age onset, degree of severity (Psoriasis Area and Severity Index), and therapy history, with positive culture of Candida spp. Conclusion: There was no difference in the number of Candida spp. colonization in the psoriasis vulgaris group and the control group. However, the culture positivity of Candida spp. in the psoriasis vulgaris patients was higher than in the control group.